The experience of cerebral palsy stigma amongst adults living in the UK and Ireland: A qualitative co-designed project - Kimberley J. Smith; Jessica Burke; Rachel Lawrence; Emily Oputa; Ruth Bailey (PLoS ONE, 2025)
Background There is evidence that cerebral palsy (CP) could be linked to stigma and discrimination, however current evidence is limited to small qualitative studies. The goal of this co-designed survey was to elicit information on experiences of stigma and discrimination amongst a larger sample of adults in the UK and Ireland. Methods Quantitative questions about sources of stigma and qualitative questions designed to elicit information on experiences of stigma were shared via an online survey. Results Eighty-six people completed the qualitative survey, and 5 themes were generated that captured experiences of stigma and discrimination. Theme 1 (rigid stereotypes) captured the lack of awareness about the heterogeneity of CP. Theme 2 (impact on participation) highlighted the difficulties that participants had with participation, particularly in terms of accessibility and sexual relationships. Theme 3 (interpersonal difficulties) included the difficulties people with CP had in interactions with the public such as feel visible in some situations, invisible in others and being infantilised. Theme 4 (systematic discrimination) highlighted discrimination in the workplace, healthcare and broader environment. Theme 5 (negative emotional impact) captured the negative emotional impact that experiences of stigma and discrimination had. Quantitative responses from 48 participants indicated that stigma was a common experience (experienced by 87.5% of respondents), and the most common sources of stigma were the public, classmates and coworkers. Conclusions Results indicate that CP is linked to experiences of stigma and discrimination which arise from a lack of understanding of the heterogeneity of CP, a public lack of awareness of how to communicate with people with disabilities, inaccessible environments and negative societal attitudes towards visible impairments. Suggested ways to tackle these issues include improving understanding of CP and removing barriers to accessibility.